A new national pregnancy policy template. (August 2018) - Rowan, Michael
Abstract : In Nov 2015, a group of representatives from the IAPM Radiation Protection SIG, the Irish Institute of Radiographers and Radiation Therapists and the Faculty of Radiologists was convened to discuss the acknowledged inconsistency in how pregnancy guidance and policy is implemented in Irish hospitals. Following on from these discussions, two national workshops was held in February and October 2016 to debate the pertinent issues with all stakeholder groups in order to guide the drafting of a new proposed national pregnancy policy. In addition to the workshops, a 3 stage national consultation process was also undertaken to refine the structure and wording of the draft document. This talk will first outline the current legislative arrangements relating to the management of women of child bearing age as well as the existing national and international guidance. It will then focus on the specific issues that were encountered and addresses during this drafting process. These include explaining risk to the patient, categorisation of high and low dose examinations, scheduling rules for high dose procedures, the layout of the pregnancy declaration form, exemptions/ruling out pregnancy, the clinical waiver, the use of pregnancy tests, radiotherapy patients, language and literacy issues, special needs patients, anaesthetised/unconscious patients and the management of minors. Proposed workflows for high and low procedures will also be presented. The final policy was approved by the governing bodies of the three organisations and published on their respective websites in November 2017.